Pengaruh Model Pembelajaran Discovery Learning Dalam Pembelajaran Daring Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi Kelas X SMA Negeri 1 Sakra Timur - Widyawati, Widyawati (CIRCULAR: Jurnal Pendidikan Sosial dan Ekonomi, 2023)
The purpose of this study was to determine the effectiveness of Discovery Learning Model in Online Learning on Student Learning Outcomes in Economics Subject at X Grade SMA Negeri 1 Sakra Timur in the Academic Year 2021/2022. The type of this study was experimental researchin the form of a quasi- experimental (quasi-experiment). The design used was two group pretest-posttest designs. There were two groups as the research samples in which one class was as a control class and one class was as an experimental class given treatment in the form of Discovery Learning model.The result of the data concluded that the average posttest score for the experimental class was 80.00, while the average posttest score for the control class was 61.21. The standard deviation (SD) for the experimental class was 4.818, while the control class was 9.416. From the hypothesis testing, it was obtained that t-count> t-table (9,276 > 1,673), so that the hypothesis Ha was accepted.It meant that there wasa significant difference before and after the treatment of learning model using Discovery Learningon the Economics learning outcomes on the subject of Market Balance and Market Structure at X grade of SMA Negeri 1 Sakra Timur in the Academic Year2021/2022